Navigating Loan Recovery Process from SMEs: Identifying Critical Challenges for Microfinance Institutions in Tanzania (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of the study is to examine the loan recovery challenges facing Microfinance Institutions (MFIs) and Small and Medium Enterprises (SMEs) in Tanzania. The study took place at Nuru Financial and Business Services (NFBS), the Self-Microfinance Fund (SMF), and Ameic Microcredit Limited (AMC). These are among the microfinance institutions found in Dar es Salaam. The researchers employed a descriptive research design and used NFBS, SMF, and AML as study cases. The study involved 50 respondents, including credit officers, obtained through simple random sampling. In the data collection, the study used semi-structured questionnaires to gather primary data. Also, the study used secondary data from documents available at NFBS, SMF, and AML. Data were analysed using simple descriptive statistics with frequency, percentages, and mean. The study found that loan recovery was a challenging task and faced several obstacles, such as insufficiency of capital to cover recovery costs, the presence of weak internal controls on loan recovery, higher interest rates, and facing an extraordinary event during the loan recovery process. Others are getting into bitter relations with customers during loan recovery due to the incompetence of staff to address loan recovery processes. Finally, the study recommends the government provide financial support or subsidies to microfinance institutions to cover recovery costs, such as grants, low-interest loans, or financial assistance programmes. Establish and enforce regulatory standards for internal controls within microfinance institutions. Implementing policies to regulate interest rates charged by microfinance institutions to ensure fairness and transparency. Establish a legal framework to handle extraordinary events during the loan recovery process. Microfinance institutions should explore partnerships with international development organisations, impact investors, or donor agencies to secure additional funding for loan recovery efforts. Loan officers should be trained in cost-effective recovery strategies, and SMEs should engage in responsible borrowing practices to minimise the risk of default.